PENGEMBANGAN VIDEO PEMBELAJARAN SENAM LANTAI GULING DEPAN BELAKANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS Ⅹ - Nova Fitriana; Lamijan Hadi Susarno; Utari Dewi (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT Practical instruction in floor gymnastics often encounters challenges due to the limited availability of learning media that enable students to independently review movement techniques beyond classroom sessions. This condition prompted the development of an instructional video covering the forward roll and backward roll for tenth-grade students at a vocational high school in Surabaya. The development process employed the Research and Development (R&D) approach using the Lee & Owens model, which consists of the analysis, design, development, implementation, and evaluation stages. Product feasibility was determined through expert validation, while its effectiveness was examined using a quasi-experimental Non-equivalent Control Group Pretest–Posttest Design. Data were collected through observations, interviews, expert validation, student response questionnaires, and cognitive and psychomotor learning achievement tests. The developed video was rated as highly feasible, receiving validation scores of 100% from the instructional design expert, 97% from the subject matter expert, and 100% from the media expert. Students also responded positively, as reflected in the small-group trial (85%) and the field trial (89%). Furthermore, the effectiveness analysis revealed a significant difference between the experimental and control groups (p < 0.05) in both cognitive and psychomotor learning outcomes. These findings indicate that the developed instructional video is not only highly feasible but also effective in improving students' learning outcomes, making it a flexible digital learning resource for supporting physical education instruction. ABSTRAK Pelaksanaan pembelajaran praktik senam lantai masih menghadapi tantangan, terutama karena keterbatasan media yang memungkinkan peserta didik mempelajari kembali teknik gerakan secara mandiri di luar jam pembelajaran. Kondisi tersebut mendorong pengembangan video pembelajaran yang memuat materi guling depan dan guling belakang bagi peserta didik kelas X di salah satu SMK di Surabaya. Proses pengembangan dilaksanakan menggunakan pendekatan Research and Development (R&D) dengan model Lee & Owens yang meliputi tahapan analysis, design, development, implementation, dan evaluation. Kelayakan produk ditentukan melalui penilaian ahli, sedangkan efektivitasnya diuji menggunakan desain quasi experiment Non-equivalent Control Group Pretest-Posttest Design. Pengumpulan data dilakukan melalui observasi, wawancara, validasi ahli, angket respons peserta didik, serta tes hasil belajar pada ranah kognitif dan psikomotorik. Produk yang dihasilkan memperoleh penilaian sangat layak dengan persentase validasi sebesar 100% dari ahli desain pembelajaran, 97% dari ahli materi, dan 100% dari ahli media. Penerimaan peserta didik juga menunjukkan kecenderungan yang positif, tercermin dari hasil uji kelompok kecil sebesar 85% dan uji lapangan sebesar 89%. Analisis efektivitas memperlihatkan adanya perbedaan yang signifikan antara kelas eksperimen dan kelas kontrol (p < 0,05) pada hasil belajar kognitif maupun psikomotorik. Temuan tersebut mengindikasikan bahwa video pembelajaran yang dikembangkan tidak hanya memenuhi aspek kelayakan, tetapi juga mampu mendukung peningkatan hasil belajar sehingga berpotensi dimanfaatkan sebagai media pembelajaran digital yang fleksibel dalam pembelajaran pendidikan jasmani.